Developing web map application based on user centered design - Petr Voldan (Geoinformatics FCE CTU, 2012)
User centred design is an approach in process of development any kind of human product where the main idea is to create a product for the end user. This article presents User centred design method in developing web mapping services. This method can be split into four main phases – user research, creation of concepts, developing with usability research and lunch of product. The article describes each part of this phase with an aim to provide guidelines for developers and primarily with an aim to improve the usability of web mapping services.